Poxvirus-based vector systems and the potential for multi-valent and multi-pathogen vaccines - Natalie A. Prow; Rocio Jimenez Martinez; John D. Hayball; Paul M. Howley; Andreas Suhrbier (Taylor & Francis Group, 2018)
Introduction: With the increasing number of vaccines and vaccine-preventable diseases, the pressure to generate multi-valent and multi-pathogen vaccines grows. Combining individual established vaccines to generate single-shot formulations represents an established path, with significant ensuing public health and cost benefits. Poxvirus-based vector systems have the capacity for large recombinant payloads and have been widely used as platforms for the development of recombinant vaccines encoding multiple antigens, with considerable clinical trials activity and a number of registered and licensed products. Areas covered: Herein we discuss design strategies, production processes, safety issues, regulatory hurdles and clinical trial activities, as well as pertinent new technologies such as systems vaccinology and needle-free delivery. Literature searches used PubMed, Google Scholar and clinical trials registries, with a focus on the recombinant vaccinia-based systems, Modified Vaccinia Ankara and the recently developed Sementis Copenhagen Vector. Expert commentary: Vaccinia-based platforms show considerable promise for the development of multi-valent and multi-pathogen vaccines, especially with recent developments in vector technologies and manufacturing processes. New methodologies for defining immune correlates and human challenge models may also facilitate bringing such vaccines to market.